Bimbingan Pranikah di Pondok Pesantren Bahrul Ulum Tambakberas Jombang Perspektif Maqoshid Syariah - Sulthon, Ahmad (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2024)
The purpose of marriage in number 1974 marriage law is “forming a happy family and eternal” then the government through the kementerian agama trying to support the purpose of the marriage by making a regulation on sakinah family, premarital guidance in boarding schools is different from those in boarding schools, premarital guidance in boarding schools is s a new method in premarital guidance. This study aims to find out how the practice of premarital counseling in Islamic boarding schools and how is maqāṣid ash-syarī'ah perspective on the guidance, From the exposure of the data in the issue of premarital guidance, there are four (4) findings of the problem being analyzed that is premarital counseling using name match counts, premarital guidance with a diploma in prayer, selametan events and premarital counseling with marriage advice. Whereas the number of actors sampled was eight (8) with different practices, the problem findings in practice when analyzed fiqh have goals that are in accordance with Islamic law.